Frequency Distribution Fitting for Electronic Documents - Arockia David Roy Kulandai (International Journal of Applied Sciences and Smart Technologies, 2021)
Studies of frequency distributions of natural language elements have identified some distributions that offer a good fit. Using electronic documents, we show that some of these distributions cannot be used to model the frequency of bytes in electronic documents even if these documents represent natural language documents.